Gewalt in Teenagerbeziehungen Erlebnisperspektiven von Jugendlichen - Stahlke, Iris (Verlag Barbara Budrich, 2019)
This empirical study shows how teenagers shape the relationship space in their first romantic relationships and how violence can occur within this social interaction. The emergence and dynamics of such relationships are described from the perspective of the teenager and the resulting preventive measures, such as e.g. B. the development and implementation of teaching units for students in grades 7 to 10. As part of a socio-psychological qualitative analysis of expert interviews from various areas of youth welfare and the police as well as school social work, cornerstones of sustainable prevention work are formulated.